2013
DOI: 10.1161/atvbaha.113.301331
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and Interleukin-1β in Ischemic Retinopathy Elicit Microvascular Degeneration Through Neuronal Semaphorin-3A

Abstract: Objective-Proinflammatory cytokines contribute to the development of retinal vasculopathies. However, the role of these factors and the mechanisms by which they elicit their effects in retina are not known. We investigated whether activated microglia during early stages of ischemic retinopathy produces excessive interleukin-1β (IL-1β), which elicits retinal microvascular degeneration not directly but rather by triggering the release of the proapoptotic/repulsive factor semaphorin-3A (Sema3A)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
136
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(163 citation statements)
references
References 53 publications
16
136
1
1
Order By: Relevance
“…1E). These observations support the concept that activated leukocytes responding to an inflammatory locus (uteroplacental unit in this case) are a significant source of IL-1, which in turn amplifies the inflammatory response (25,33); accordingly, the systemically administered large molecule Kineret (17.5 kDa) is effective on blood leukocytes, but contrary to 101.10 seems to have limited access to intrauterine/placental IL-1R wherein inflammation is triggered (by IL-1), consistent with documentation on IL-1 (∼17.5 kDa) (34, 35).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…1E). These observations support the concept that activated leukocytes responding to an inflammatory locus (uteroplacental unit in this case) are a significant source of IL-1, which in turn amplifies the inflammatory response (25,33); accordingly, the systemically administered large molecule Kineret (17.5 kDa) is effective on blood leukocytes, but contrary to 101.10 seems to have limited access to intrauterine/placental IL-1R wherein inflammation is triggered (by IL-1), consistent with documentation on IL-1 (∼17.5 kDa) (34, 35).…”
Section: Resultssupporting
confidence: 85%
“…We previously showed that actions of 101.10 required presence of the ubiquitous IL-1RI (25). Accordingly, in this study again 101.10-FITC colocalized by immunohistochemistry with IL-1RI on the myometrial cell line hTERT-C3 and the macrophage cell line RAW-Blue mouse macrophages (Supplemental Fig.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Moreover, the context in which NLRP3 may participate in uveitis is more complicated beyond what is modeled by direct activation of TLR4. NLRP3 has been reported to be involved in other types of eye diseases such as ischemic retinopathy [34] and agerelated macular degeneration [35], an ocular disease whose association with inflammatory processes is increasingly being elucidated. Thus, it seems entirely likely that NLRP3 participates in other aspects of uveitis, especially since this pathway is known to play a role in shaping pathogenic Th17 effector responses.…”
Section: Short Communicationmentioning
confidence: 99%